Pengaruh Penerapan Good Corporate Governance dan Gaya Kepemimpinan pada Kinerja Keuangan - Arina Pratiwi, Putu Dewi; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p22, 2018)
Implementation of the principles of Good Corporate Governance and Leadership Style is expected to produce better financial performance of village credit institutions (LPD). GCG principles include Transparency, Accountability, Responsibility, Independence, and Fairness. This study aims to determine the application of good corporate governance and leadership style on the financial performance of LPD. This research uses non probability sampling sampling method as well as data collection with questionnaire technique spread to 35 LPD and each taken three responders in each LPD Se-Kota Denpasar. Analytical technique used is multiple linear regression, and previously done instrument testing and classical assumption test for the accuracy of regression analysis results. Based on the results of hypothesis testing is known that the implementation of Good Corporate Governance has a positive and significant influence and leadership style have a positive and significant impact on the financial performance of LPD in Denpasar. Keywords: good corporate governance, leadership style, village credit institutions, return on assets, financial performance